2013
DOI: 10.1016/j.cbi.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinetic alcohol dehydrogenases make yeast fitter for growth in the presence of allyl alcohol

Abstract: Previous studies showed that fitter yeast (Saccharomyces cerevisiae) that can grow by fermenting glucose in the presence of allyl alcohol, which is oxidized by alcohol dehydrogenase I (ADH1) to toxic acrolein, had mutations in the ADH1 gene that led to decreased ADH activity. These yeast may grow more slowly due to slower reduction of acetaldehyde and a higher NADH/NAD+ ratio, which should decrease the oxidation of allyl alcohol. We determined steady-state kinetic constants for three yeast ADHs with new site-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…The result showed that alginate produced the highest enzyme activity. This conclusion was different from other literature 22 , which commonly used glucose as the carbon source of alcohol dehydrogenase fermentation. In the subsequent experiments, alginate was also used as fermentation medium carbon source.…”
Section: Fermentation Conditions Of Alcohol Dehydrogenasecontrasting
confidence: 99%
See 1 more Smart Citation
“…The result showed that alginate produced the highest enzyme activity. This conclusion was different from other literature 22 , which commonly used glucose as the carbon source of alcohol dehydrogenase fermentation. In the subsequent experiments, alginate was also used as fermentation medium carbon source.…”
Section: Fermentation Conditions Of Alcohol Dehydrogenasecontrasting
confidence: 99%
“…In the process of enzyme fermentation, temperature control is very important, because the microbial growth and enzyme fermentation production need certain temperature conditions 23 . Different cells have their optimum growth temperature.…”
Section: Fermentation Conditions Of Alcohol Dehydrogenasementioning
confidence: 99%
“…Thus, in the presence of allyl alcohol, yeast reduce YADH activity, even though it means slower growth [ 118 ]. Lower rates of acetaldehyde reduction result in an increased intracellular ratio of NADH/NAD + , thereby protecting the cell against acrolein toxicity [ 119 ]. Through genetic sequencing, specific YADH mutants were identified in yeast with improved fitness in allyl alcohol due to decreased acetaldehyde reduction [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Thermoanaerobacter ethanolicus , three ADHs play different roles during ethanol formation ( Zhou et al, 2017 ). In yeast, ADH1 is responsible for ethanol production from acetaldehyde and NADH, contributing to fungal growth in the presence of alcohol ( Plapp et al, 2013 ). Yeast ADH2 converts the ethanol accumulating to acetaldehyde under anaerobic conditions ( de Smidt et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%